To Evaluate the Role of MRI in Assessment of Myelopathy - Ashish Shukla; Prashant U Titare; Varsha Rote Kaginalkar; Ajay Vare; Anjali Pawar; Vandana Bhatt (Asian Journal of Medical Radiological Research, 2019)
Background: Myelopathy is a disease of spinal cord which can lead to significant neurological morbidity. MRI because of better soft tissue differentiation, not only helps in determining the cause of myelopathy but also plays significant role in their management..Subjects and Methods: A cross sectional study was done on 80 patients in our institute between June 2017 to October 2018. All patients having complaints of pain in the back with sensory or motor dysfunction or both, having suspicion of myelopathy, referred to the department of Radio-diagnosis for MRI spine evaluation. MRI scan performed on 1.5 Tesla PHILIPS ACHIEVA machine, standard surface & body coils were used for acquisition of images. Results: In this study out of 80 patients of myelopathy, 65% were due to cord compression and 35% were due to non compressive causes. Involvement of cervical spine was more common than the thoraco-lumbar spine. Most common condition associated with compression of the cord was Degenerative spine disease followed by Potts spine and trauma. Under the causes of Non compressive myelopathy- Myelitis was the most common cause, which was seen most in Isolated cases followed by associations with Multiple sclerosis and Neuromyelitisoptica. Conclusion: MRI is the mainstay modality to diagnose spinal cord pathologies.Degenerative spine disease was the most common cause of compressive myelopathy and Myelitis was the most common cause of Non compressive myelopathy. Early diagnosis using MRI improves the prognosis of myelopathy.